ANALISIS PUTUSAN TERHADAP TINDAK PIDANA PEMALSUAN SURAT KETERANGAN SAHNYA HASIL HUTAN KAYU DI KABUPATEN SIDENRENG RAPPANG (Studi Kasus Putusan No.58/Pid.B/LH/2022/PN Sdr) - Arya Saputra A.R, Ardhi; Asli Abu, Yudri (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2024)
This study aims to describe the verdict on the crime of forging the certificate of legality of timber forest products in Sidenreng Rappang district, with a research method with a normative-empirical approach by conducting normative case analysis and interviews, as for the research results; 1). The impact of the Crime of Forgery of Certificates of Legality of Timber Forest Products is the occurrence of deforestation, the destruction of this Forest Ecosystem, then climate change and global warming will be more severe, Economic Losses on Regional Income, Providing a Deterrent Effect on Perpetrators. while Factors influence a person to commit the crime of forging the Certificate of Legality of Timber Forest Products, namely; Financial Advantages and Weak Law Enforcement Supervision.